PERAN PENYIDIK RESERSE KRIMINAL UNIT II (DUA) POLISI RESOR PELALAWAN DALAM PENANGANAN TINDAK PIDANA PERUSAKAN HUTAN DI WILAYAH HUKUM POLRES PELALAWAN - SRI RAHAYU; Mexsasai Indra; Erdiansyah ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Pelalawan which is one of the districts in the province of Riau . This district suffered very severe damage to forests , this is caused by the illegal logging and burning of land carried out by the responsible party. actions taken by police investigating criminal detectives Pelalawan resort is to take some action. District detectives investigate criminal conduct investigations for violations of illegal logging and the inspection is to catch and hold the perpetrators of crimes against forest destruction , investigators also seized evidence that is used to destroy forests conducted by parties who are not responsible , but the implementation of the role of police investigators kiriminal resorts Palalawan have not done as we expected because there are still many obstacles faced by investigators in handling the destruction of forest.Cnstraints experienced by the investigator in the prevention of deforestation in Pelalawan district is limited means and facilities to prevent the destruction of forests , such as operational vehicles , investigators were lacking , and the funds are limited and difficult to find evidence and perpetrators of the forest . Eforts made to overcome the obstacles existing by adding facilities and infrastructures , adding police investigation , proposed budget for the cost of the process of investigation and repression of acts of criminal damage to forests , while also coordinating with related agencies such as the local community as well as investigators more , and to supervise and patrols in areas prone to illegal logging .Keywords : Investigation - Crime - Forest Destruction